Bahtsul Masail sebagai Mazhab Fikih NU: Sebuah Perspektif - Muhammad Adib; Syamsul A'dlom (Fakultas Syariah - IAI Al-Qolam Malang, 2018)
This paper talks about the system of fiqh schools in Bahtsul Masail, especially in the context of the institution-based trend of fiqh schools in the modern era. Based on historical, normative, and sociological perspectives, this paper concludes that Bahtsul Masail has created a distinctive and unique system of fiqh schools, so that it has strong arguments to be called “the NU fiqh school”